Analysis of interrelation between water quality and hydrologic conditions on a small karst catchment area of sinking watercourse Trbuhovica - Hinić, Višnja; Rubinić, Josip; Vučković, Ivan Ružić, Igor; Gržetić, Ana Volf, Goran; Ljubotina, M. Kvas, Nena (2009)
Sinking watercourse Trbuhovica is located at the topping karst of Gorski Kotar in Croatia, near the Slovenian border. About 900 inhabitants live in Trbuhovica catchment area. Sewage system had not been built. The project KEEP WATERS CLEAN (INTERREG III A project) was approved by EU commission and has a purpose of investigating water resources of that area, their appropriate protection and improving management of those resources. This paper presents project's 1st phase investigation results: hydrologic conditions and water quality at several locations on stream and at the springs of Trbuhovica, Mlake and Obrh. Climatologic (precipitation, air temperature and snow cover), basic hydrologic characteristics (flow and water temperature), water quality parameters (pH, electric conductivity, alkalinity, oxygen regime, nutrients and mineral oils) and microbiology indicators have been monitored. Samples of micro invertebrates and samples of periphyton have been collected in the field. Biological results have been elaborated via Saprobial Index according to Pantle-Buck. Analyses results showed a strong connection between hydrologic condition and selected water quality parameters. The groundwater quality changes are very quick. Maximum pollutions occur during the period of intensive rain. Water at the spring of Mlaka is very clean and is classified in the first to second water category, while Trbuhovica shows higher organic pollution.
Projekt MZOS
Projekt MZOS
ENG